Consumer preferences for safe pork products in rural Kenya - Gichuyia, Cianjo M.; Mtimet, Nadhem; Akaichi, Faical; Onono, Joshua O.; Fèvre, Eric M.; Thomas, Lian F. (2021)
Food-safety is classified as a basic human right and is therefore controlled and regulated by governments. Some governments however, due to resource constraints and the diverse nature of the food in their countries, fail to enforce appropriate legislation. To remedy such situations, studies have suggested alternatives to government intervention which leverage market incentives to achieve greater efficiency in food safety management. These incentives are largely determined by consumers preference and their willingness to pay for safer food. Rural pork value chains in Kenya are mostly low input systems with several public health inadequacies which pose a threat to the health of consumers as well as other livelihood systems dependent on pork production. This is a common characteristic of livestock production in developing countries where smallholder production and informal marketing systems are quite dominant. This study analyses the preferences and willingness to pay for safe and high quality pork products by consumers in such a system. Results indicate that consumers in Kenya state a preference for safer pork products and a willingness to pay more for them. These highlight a potential opportunity to exploit market based incentives such as a ‘safe pork’ premium to encourage a certain degree of self-regulation of meat value chains. Additionally, investing in increasing consumer awareness about food safety issues should be considered in order to generate an effective market demand especially in rural areas with relatively lower literacy levels.